Prevalence of depressive symptoms among first-year undergraduate students of government medical and engineering colleges in Thiruvananthapuram city - Jisnu Janardhanan; Rithwik Santhosh; Ashoka; Hyder, Shafeen (Asian Journal of Medical Sciences, 2024)
Background: Depression is a major health issue globally and is on par with lifestyle diseases such as diabetes and hypertension when it comes to morbidity. The first year in professional college is a critical transition period encompassing drastic biological, social, emotional, and academic changes which could be potential stressors for precipitating depressive symptoms. Aims and Objectives: The current study aims to find the prevalence of depressive symptoms among 1st-year undergraduate students of Government medical and engineering colleges in Thiruvananthapuram city. Materials and Methods: The cross-sectional study included 88 medical students and 212 engineering students. Patient Health Questionnaire-9 was used to assess depressive symptoms, brief resilience scale to assess resilience, and CRAFFT 2.0 to screen for substance use. SPSS was used for the analysis of data; Chi-square test was used for the comparison of proportion and t-test for comparing means. Results: 28% of total study subjects reported depressive symptoms. One in three medical students reported depressive symptoms while one in four engineering students reported depressive symptoms. Low resilience had negative association and history of substance use had positive association with the presence of depressive disorders. Conclusion: A significant number of students in professional colleges have depressive symptoms, either diagnosed or undiagnosed. Steps can be taken in the direction of reducing academic distress, promoting extra-curricular activities, setting up student support programs in institutions, legal policies to limit substance misuse among students, and creating awareness about positive parenting styles which give adequate importance to self-care and being mindful.